Behavior Analysis of Legislators in Health Planning in South Sulawesi Province - Indar; Arifin, Muhammad Alwy; Nurhayani, Nurhayani; Mallongi, Anwar (International Journal of Criminology and Sociology, 2021)
Health is political because its social determinants are easily accepted in political intervention. Therefore, the health system of a region mandates that health development will take place well if it is supported by good and targeted planning. The purpose of this study is to analyze the behavior of legislators in planning health services in South Sulawesi Province. The research was conducted in the DPRD of Makassar City and Bantaeng Regency. This type of research is a qualitative research. Data was collected using in-depth interviews, observation and document review. Data processing was carried out using triangulation and content analysis methods. The results showed that based on indicators of knowledge, attitudes, perceptions and actions of legislators were in the poor category. In addition, it was known that there was an interest from legislators in terms of health planning, but this interest was indirectly in the interest of improving public health status.